2021
DOI: 10.5194/acp-21-12227-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Saccharide composition in atmospheric fine particulate matter during spring at the remote sites of southwest China and estimates of source contributions

Abstract: Abstract. Based on source-specific saccharide tracers, the characteristics of biomass burning (BB) and biogenic emissions of saccharides were investigated in three rural sites at Lincang, which is 65 % covered with forest in the southwest border of China. The total saccharides accounted for 8.4 ± 2.7 % of organic carbon (OC) and 1.6 ± 0.6 % of PM2.5. The measured anhydrosugars accounted for 48.5 % of total saccharides, among which levoglucosan was the most dominant species. The high level of levoglucosan was b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 97 publications
1
6
2
Order By: Relevance
“…4). Averages of the sum of mannitol and arabitol concentrations measured in the three sampling locations (75 ng m −3 ) were higher than those reported in the megacity of Beijing (21 ng m −3 ) (Kang et al, 2018) and the rural site of Lincang, China (21.5 ng m −3 ) (Wang et al, 2021). Since these sugar polyols are reported to be abundant in fungi, trees, branches, and leaves (Wang et al, 2021;Fu et al, 2008), the high abundance of mannitol and arabitol found in this study can be attributed largely to a biological origin.…”
Section: Resultscontrasting
confidence: 63%
See 4 more Smart Citations
“…4). Averages of the sum of mannitol and arabitol concentrations measured in the three sampling locations (75 ng m −3 ) were higher than those reported in the megacity of Beijing (21 ng m −3 ) (Kang et al, 2018) and the rural site of Lincang, China (21.5 ng m −3 ) (Wang et al, 2021). Since these sugar polyols are reported to be abundant in fungi, trees, branches, and leaves (Wang et al, 2021;Fu et al, 2008), the high abundance of mannitol and arabitol found in this study can be attributed largely to a biological origin.…”
Section: Resultscontrasting
confidence: 63%
“…To accurately qualify the BB source in different locations, nss-K + has also been used as a typical tracer of BB in previous studies (Kunwar and Kawamura, 2014). However, previous studies also indicated that soil dust could be another source of water-soluble nss-K + in aerosols (Urban et al, 2012(Urban et al, , 2014Wang et al, 2021). The nss-K + concentrations averaged 633.1 ng m −3 in the urban area, which was higher than those observed in the rural (549.6 ng m −3 ) and forest (590.2 ng m −3 ) areas.…”
Section: Identify Classes Of Combustion Sourcesmentioning
confidence: 99%
See 3 more Smart Citations